Palynological Study of the Genus Arabis l. (Brassicaceae) in Iraq - Khazal Dh. Wadi Al-Jibouri (Journal of Global Pharma Technology, 2016)
Pollen morphology of 4 species (A. aucheri , A. auriculata, A. caucasica, A. nova) belonging to the genus Arabis L. in Iraq was examined by light microscope and scanning electron microscope to determine the significance of pollen features as a taxonomic characters. The results showed pollen grains of the species were monades, homopolar, tricolpate, and with medium size, but the species varied in shapes (polar and equatorial view), colpus length and width, exine thickness and exine ornamentation. Pollen colors were brown convert to brownish yellow.Keywords: Arabis, Cruciferae, Palynology, Pollen grain.